(3GdfTQ GdfOi HMbjbI GHf YHO GdhgGH GdfLOis - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s ((3MSf Hf YHO Gddg Hf YHO GdcQje GdCchY s)
(3ChdgG (B:s
(3eGRGdJ JHdZfG GdCNHGQ ef SfI SJjf heGFI Cda HCfg XgQ ai fLO QLd jOYh Edi EJHGY GdSfI GdfHhjI hjfgi Yf GdEHJOGY s
(3BNQgG (B:s
(3GdMeO ddg ced GdeQGO hGdMeO ddg GdbGgQ MLJg GdWGgQI eMLJg hjNdY YdfjG NdY GdgOGjI hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GNJdGa GdabgGAs